Pengaruh Job Involvement dan Job Satisfaction terhadap Organizational Citizenship Behaviour serta Dampaknya pada Knowledge Sharing di PT Indolift Sukses Abadi - Tinjung Desy Nursanti; Ebenhaezer Samudera; Fajar Widiansyah (Binus Business Review, 2015)
The research was conducted at PT Indolift Sukses Abadi, a folklift distributor that sells and distributes all heavy equipment products. The objective of this study was to determine whether there is any influence of job involvement and job satisfaction on organizational citizenship behavior that impact to knowledge sharing. Data were obtained by distributing a questionnaire to 100 respondents of the company; and then were processed using Path Analysis Technique. Based on this research, job involvement and job satisfaction partially and simultaneously have influence on organizational citizenship behaviour. Then, job satisfaction and organizational citizenship behaviour partially have influence on knowledge sharing. However, job involvement partially has no influence on knowledge sharing. Nevertheless, job involvement, job satisfaction, and organizational citizenship behavior simultaneously have influence on knowledge sharing.